PENGARUH PENYULUHAN PIJAT B AYI DAN BALITA TERHADAP TINGKAT PENGETAHUAN IBU - Dewi Aprilia Ningsih (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2022)
Baby massage is a slow and gentle massage throughout the baby's body starting from the legs, stomach, chest, face, hands, and back. Mother's knowledge about infant massage independently needs to be increased considering the many benefits obtained from infant massage. This study aims to study the effect of counseling on infant and toddler massage on mother's level of knowledge. This type of research is a quasi-experimental with a pre-experimental design using a one group pretest posttest design approach. The population in this study were all mothers who had infants and toddlers aged 0-12 months, 80 mothers were taken by accidental sampling. The results of the study were from 80 mothers who had babies and toddlers aged 0-12 months in the Bentiring Health Center working area, Bengkulu City, prior to being given counseling, knowledge about infant massage was at a low level of knowledge with an average value of 8.06. From 80 mothers who have babies and toddlers aged 0-12 months in the working area of ​​Bentiring Public Health Center, Bengkulu City, after being given counseling, the knowledge about baby massage is in sufficient knowledge with an average value of 11.05. Wilcoxon statistical test results obtained a value of Z = -7.064 with p-value = 0.000 <0.05 significant, meaning that there is a difference in knowledge scores before and after counseling, there is an effect of counseling on infant and toddler massage on mother's level of knowledge. It is hoped that the health team, especially midwives, can optimize the provision of information related to how to do independent baby massage using media such as leaflets, alternating sheets, or the use of videos. So that mothers can better understand and understand what is conveyed by the midwife or puskesmas officer because changes in the way information determine the success of activities. . Keywords: Baby Massage, Counseling, Knowledge